Embolization of Cavernous Sinus Dural Arteriovenous Fistula (CSDAVF) via transvenous approaches: Practice, experience summary and literature review. (July 2021) - Zhang, Shuai; Wang, Jiejun; Liu, Dong; Lv, Ming
Highlights: The safety and efficacy of embolization via transvenous approaches was evaluated. At the same time, we introduced our clinical experience in applying transvenous approaches. We also explored the selection strategies of these transvenous approach. Abstract: Objective: To evaluate the safety and efficacy of embolization via transvenous approaches in patients diagnosed with Cavernous Sinus Dural Arteriovenous Fistula (CSDAVF). We also hope to further summarize our preliminary experiences with transvenous approaches. Material and methods: We retrospectively collected data from patients who were diagnosed with CSDAVF and were treated with embolization via transvenous approaches from June 2014 to November 2020 at Beijing Tiantan Hospital. We evaluated the safety and efficacy of this treatment using radiological results and clinical follow-up. Results: A total of 83 patients were included in this study. Complete occlusion was obtained in 76 (89.4%) patients. Sub-total occlusion was obtained in eight (9.4%) patients. Partial occlusion was obtained in one (1.2%) patient. There was no recurrence. Seventy-six patients (91.5%) were cured, and seven patients showed symptom improvement (8.5%). There were no cases of worsening symptoms following embolization, and only ten (12.0%) cases had mild complications. Conclusion: There was a high occlusion rate and a low complication rate in our study. Thus, completing embolization of CSDAVF via transvenous approaches may be safe and effective. However, this operation is more difficult than those via transarterial approaches. Transvenous embolization should therefore be performed in an experienced medical center.